Cell-based measurement of neutralizing antibodies against adeno-associated virus (AAV) - Jungmann, Andreas; Müller, Oliver J.; Rapti, Kleopatra (Cardiac gene therapy, 2017)
In recent years gene therapy using adeno-associated viral (AAV) vectors to treat cardiac disease has seen an unprecedented surge, owing to its safety, low immunogenicity relative to other vectors and high and long-term transduction efficiency. This field has also been hampered by the presence of preexisting neutralizing antibodies, not only in patients participating in clinical trials but also in preclinical large animal models. These conflicting circumstances have generated the need for a simple, efficient, and fast assay to screen subjects for the presence of neutralizing antibodies, or lack thereof, in order for them to be included in gene therapy trials.